2008
DOI: 10.1157/13120396
|View full text |Cite
|
Sign up to set email alerts
|

Immediate allergic reactions by polyethylene glycol 4000: two cases

Abstract: The evacuant solution (ES) is a drug that has been used to clean the colon. The most common described side effects when using this drug are abdominal symptoms; skin rash is rare. We report on two patients who presented urticaria and angioedem after the intake of an evacuant solution to make a rectoscopy. We performed allergy studies: skin prick tests with common inhalants, pure ES and the components (polyethylene glycol 4000 (PEG 4000), KCI, NaCO3, NaPO3, NaSO3, NaCI, neohesperydine, potasic acesulfam and oran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Anton Gironés et al described 2 additional cases of immediate reactions to PEG‐4000 and confirmed these by oral challenge . Interestingly, both patients had negative skin prick testing to PEG‐4000, and after a positive challenge, the authors then performed intradermal testing, which was positive . Other reports have suggested systemic reactions to PEG.…”
Section: Discussion and Literature Reviewmentioning
confidence: 93%
See 1 more Smart Citation
“…Anton Gironés et al described 2 additional cases of immediate reactions to PEG‐4000 and confirmed these by oral challenge . Interestingly, both patients had negative skin prick testing to PEG‐4000, and after a positive challenge, the authors then performed intradermal testing, which was positive . Other reports have suggested systemic reactions to PEG.…”
Section: Discussion and Literature Reviewmentioning
confidence: 93%
“…Fisher et al described 2 cases of immediate reactions to PEG 300 and 400 that produced negative patch testing, but rubbing the respecting agents on the patients— forearms produced an urticarial reaction within 15 minutes . Anton Gironés et al described 2 additional cases of immediate reactions to PEG‐4000 and confirmed these by oral challenge . Interestingly, both patients had negative skin prick testing to PEG‐4000, and after a positive challenge, the authors then performed intradermal testing, which was positive .…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…1 Polyethylene glycol 4000 has been associated with anaphylactic reactions and may have been the causative factor in the case reported here. 5 Anaphylactic reactions to long-acting injectable antipsychotics in patients with established tolerance of oral formulations, although rare, have been reported and attributed to ingredients of the injectable formulations. 6 One published case report described an anaphylactic reaction, manifesting as rash and wheezing, after the first dose of long-acting injectable risperidone in a patient with confirmed tolerance of oral risperidone; the report's authors attributed the reaction to the polymer that encapsulated the risperidone in the long-acting injection.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of anaphylaxis following the use of HMW macrogols have been reported, with most being related to their use as lavage solutions for bowel preparation [ 63 66 ]. The Allergy Vigilance Network recorded five cases of severe macrogol-related anaphylaxis from 2010 to 2012, including two cases with macrogol 4000 (one presenting as generalized urticaria following treatment with 10 g, and one as anaphylactic shock following treatment with 20 g) [ 64 ].…”
Section: What Is the Tolerability Profile Of Macrogol 4000?mentioning
confidence: 99%